Analisis Kelayakan Investasi pada Studi Kasus Perusahaan Properti Ciputra Group Menggunakan Metode Cost Benefit Analysis - Shauma Salsabiilla, Risqi’a; Oktar, Adnan; Rahmawati, Febri; Alif. S, Muh Ikhsan (LPPM ITK, 2025)
The purpose of this study is to analyze the investment feasibility of Ciputra Group real estate projects using Cost-Benefit Analysis (CBA). Secondary data in the form of financial statements of Ciputra Development Tbk from 2005-2023 were used with the analysis tools of Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit Cost Ratio (BCR). The project is assumed to have a four-year investment period (2020-2023). The analysis results show that the project is worth investing with a positive NPV of IDR5.37 trillion, an IRR of 3.4512% which is higher than the discount rate of 3%, and a BCR of 1.22. In addition, a sensitivity analysis was conducted to measure how changes in assumptions affect the results. The findings recommend investing in Ciputra Group's real estate projects as they have the potential to provide significant economic benefits to the company.